Use of novel postmortem sample types for detection of African swine fever virus infection after natural consumption - Deavours, Aubrey Dawn (Kansas State University, 2023)
African swine fever virus (ASFV) is a recognizable disease by the World Organization for Animal Health (WOAH). Virulent strains can cause 100% mortality in pigs and with no current licensed vaccine or therapeutic, rapid identification, biocontainment, and culling is critical. First discovered in Africa in the 1920s, ASFV has spread rapidly through the continent and into other countries. Since its first introduction into China in 2018, ASFV has rapidly spread across the country and into additional countries such as Germany in 2020. In 2021, the virus was detected in the Dominican Republic, due to its geographical location in respect to the United States, the U.S is on heightened alert. The United States is an ASFV naïve country and relies on mitigation strategies and trade restrictions to maintain that status. Current confirmatory testing for ASFV for postmortem requires spleen, tonsil, gastrohepatic lymph node, renal lymph node, and inguinal lymph node. These samples are not often collected on farms and may be difficult to collect during passive surveillance due to decomposition of a wild boar carcass. It is critical to have validated, consistent practices that can be applied to a wide variety of circumstances. Having more samples validated for the detection of ASFV will improve rapid and reliable detection while also reducing further environmental contamination posed from opening a carcass. This study sought to identify novel sample matrices, that were equivalent to the postmortem sample spleen, for the detection of ASFV Georgia/07 in pigs’ that orally consumed ASFV inoculated media. In our experiment, 7-8 week of male pigs (n=10), orally consumed media with 10⁴ TCID₅₀/ml (tissue culture infectious dose) ASFV Georgia/07, along with controls (n=2), who received sterile non-infectious media. After presentation of clinical signs between 5-7 dpi, pigs were humanely euthanized, and a variety of tissues were immediately collected. This study compares log₁₀ Starting Quantity (SQ) copy numbers of ASFV Georgia/07 generated from real-time PCR to assess quantity of ASFV DNA present in: swabs (preputial, spleen, muscle, peritoneal fluid, conjunctiva), lymph nodes (mesenteric, gastrohepatic, inguinal, popliteal, submandibular, tracheobronchial, retropharyngeal, sternal), fluid (ocular, urine, feces), and tissues (spleen, tonsil, conjunctiva, muscle, ear notch, tail notch, bone marrow, diaphragm) to the gold-standard postmortem sample of spleen. After collection, samples were processed and stored immediately in -80° C until DNA extraction and PCR was performed. Samples were evaluated using paired t-Test (p ≤ 0.05) and were individually compared to not only spleen but also other samples with similar mean SQ values and variance for quantity of ASFV DNA present. These multiple comparisons will provide additional information for field veterinarians, hunters, and slaughterhouse staff to select an accessible and available tissue with confidence that it is comparable to the SQ of the spleen or other reliable matrix for the early detection of ASFV.
Keywords: African swine fever virus; Georgia/07; Novel sample